EFEKTIVITAS KONSELING KELOMPOK DENGAN TEKNIK TIME MANAGEMENT UNTUK MENIMALISIR PROKRASTINASI MENGHAFAL AL-QUR’AN DI PONDOK PESANTREN KHUSUS YATIM AS-SYAFI’IYAH - Yudi Supriyadi; Dwi Endrasto Wibowo (Guidance : Jurnal Bimbingan dan Konseling, 2019)
This research aims to examine the effect of Effectiveness of Group Counseling with Time Management Techniques to Minimize the Procrastination of Memorizing Al-Qur'an.This method used is Quasi Experiment with the design Pretest-Posttest Control Group Design. Involve 18 students, 9 students as an Experiment Group and 9 other students as a Control Group. The data results that (F= 9.377; p<.000) Means H0 ia rejected and H1 is accepted. The conclusion of the data is Group Counseling with the Time Management is Effective in Minimazing the Procrastination of Memorizing Al-Qur'an.